Density functional computational and X-ray studies on pharmaceutical compound 1-{3-[4-(4-fluorophenyl)piperazin-1-yl]propyl}-1H-indole - Şahin, Zarife Sibel; Yarım, Mine; Köksal, Meriç (European Journal of Chemistry, 2017)
The crystal and molecular structure of 1-{3-[4-(4-fluorophenyl)piperazin-1-yl]propyl}-1H-indole (I) has been determined by single-crystal X-ray diffraction. Molecular geometry of compound I in the ground state has been calculated using the density functional method (DFT) with B3LYP/6-31G(d,p) basis set and compared with the experimental data. In addition, density functional calculations of the structure, molecular electrostatic potential map, frontier molecular orbitals, atomic charges, thermodynamic functions and global chemical reactivity descriptors of compound I were performed.